Effect of Social Media Usage and Entrepreneurial Marketing on The Success of Organic Processed Food MSMEs - Nanda Nur Rafiana; Ma’mun Sarma; Mukhamad Najib (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Social media usage has been adopted by entrepreneurs to achieve business goal. The rise of health and sustainability awareness has opened an opportunity for entrepreneurs to start organic processed food business despite the marketing obstacle about organic food informations. Entrepreneurial marketing is considered as a more appropriate marketing approach for limitation in MSMEs which is able to indicate the perception of entrepreneurs who use the social media for overcoming technology and information resource obstacle. This study was aimed to analyze effect of social media usage and entrepreneurial marketing on the success of organic processed food MSMEs based on the analysis of Structural Equation Modelling (SEM) with Partial Least Squares (PLS). The study was conducted on Komunitas Organik Indonesia in Greater Jakarta (Jabodetabek) with a total population of 400 MSMEs from December 2020 to March 2021. The data source used was primary data that was collected from 63 respondents which use social media on business need. Based on result of SEM analysis, the use of social media for marketing, customer relation and service, and accessibility of information have a significant and positive effect on entrepreneurial marketing. Moreover, social media usage for marketing and information accessibility was found to have direct effect which could increase business success even though social media usage for customer relation and service did not affect business success. On the other hand, entrepreneurial marketing also directly influenced business success. The use of social media together with application of entrepreneurial marketing will have effect on business success. Keywords: social media usage, entrepreneurial marketing, business success, MSMEs of organic processed food, SEM-PLS